2020
DOI: 10.1155/2020/8873962
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Decentralized VS Centralized Control for the Traffic Signal Synchronization Problem

Abstract: This paper suggests the adoption of a spatial decomposition method to solve the signal synchronization problem. A good signal setting maximizes the number of vehicles passing through intersections, while minimizing gas emissions and possible delays experienced by drivers. The signals synchronization issue can be defined as the problem of finding the offsets, the green timings, and the cycle length for a series of controlled intersections, minimizing the total delay of the network subject to admissibility const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…The use of traffic signal synchronization is used to control traffic signals in clusters wherein all signals in one cluster follow the same phase pattern. This is a popular approach in the literature, as traffic signal synchronization may be used to improve the flow of traffic along heavily traveled routes [42]. For networks composed of more than 4 intersections, a signal synchronization scheme of k clusters is fixed, as shown in Figure 6 for a 12-node network.…”
Section: G Model Assumptionsmentioning
confidence: 99%
“…The use of traffic signal synchronization is used to control traffic signals in clusters wherein all signals in one cluster follow the same phase pattern. This is a popular approach in the literature, as traffic signal synchronization may be used to improve the flow of traffic along heavily traveled routes [42]. For networks composed of more than 4 intersections, a signal synchronization scheme of k clusters is fixed, as shown in Figure 6 for a 12-node network.…”
Section: G Model Assumptionsmentioning
confidence: 99%
“…Network decomposition is highlighted in recent DSC research [2] as an important factor for optimizing DSC system. In this work, a grid network is decomposed into grid subnetworks.…”
Section: Network Decompositionmentioning
confidence: 99%
“…us, computational time (CT) is the point of comparison for the performances of the centralized signal control (CSC) and decentralized signal control (DSC) systems. In addition, studies have shown network decomposition to have a significant impact on system performance [2,3]. erefore, we investigate the performance of CSC and DSC systems under different decomposition setups, using test scenarios constructed with varying demand profiles and grid networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, traffic monitoring is one of the most valuable functions of traffic management systems (TMSs). Particularly in advanced TMSs (ATMSs), real-time collection of precise information through traffic monitoring plays a crucial role for traffic managers when they develop various control strategies [1][2][3]. Furthermore, the detailed numerical status of realtime traffic such as lane-by-lane travel volume and queue length can be used as supplementary information for cooperative intelligent transportation system (C-ITS) operations based on autonomous vehicles [4,5].…”
Section: Introductionmentioning
confidence: 99%